Measures to be taken to raise Azerbaijan’s rating in the field of digitalization and public services in international rankings - Askarli, Madina; Talibov, Samir; Baghirova, Sama (ADA University, 2022)
In recent decades the development of E-government has been in the focus of government development programs worldwide. As Azerbaijan is also rapidly developing in the sphere of digitalization of public services, advancement in the international rankings related to this field is among policies prioritized in the government agenda. This capstone project aims to provide policy options that would contribute to the advancement of Azerbaijan in Global Innovation Index (GII) and EGDI (E-Government Development Index) international rankings evaluating e-government development of the countries worldwide. The development of ICT (Information and Communications Technology) indicator of Infrastructure pillar of the GII was selected as a focus of the project. All subpoints of the ICT indicator were analyzed both in Azerbaijan and in two selected best practice countries, Estonia, and Kazakhstan. Further, based on these practices possible policy options were proposed and examined based on feasibility of each one of them in the context of Azerbaijan. Lastly, the recommendations were proposed grounded on the prioritization of these policy options considering the feasibility in Azerbaijan in the short run. Firstly, the findings of the project propose enhancement and further development of ASAN Bridge platform by integrating more private and public agencies. Second, improvement of the existing technology parks and free economic zones like STP and AFEZ through attraction of more innovative technologies and equipment. Finally, the project suggests the technical changes to the ASAN Müraciət and Rəqəmsal İcra Hakimiyyəti (RİH) platforms, thus facilitating the accessibility of those systems to the citizens.
Keywords: E-government.; E-government -- Azerbaijan.; ICT.; Public and International Affairs